HUBUNGAN ANTARA PENGAWASAN KEPALA SEKOLAH DAN KOMPENSASI GURU TERHADAP KINERJA GURU DI SMA - Padi Padi Padi (Manajer Pendididikan, 2016)
The objective of this research is to find out whether of the monitoring by the performance of teachers, determine the relationship of compensation to the performance ofteachers, and determine the relationship of supervision and compensation along with teacher performance. The samples of the study were 33 respondents in high school state 1 Ketahun and teacher as the population of this study. The method of this study was descriptive Correlation. The results of this study showed that (1) there is a positive correlation between the control (X1) with the performance of teachers (Y); (2) there is a positive correlation between compensation (X2) andteacher performance (Y); and (3) there is a positive correlation between the control (X1) and compensation (X2) together with the teacher's performance (Y).Keywords: supervision, compensation, performance of teachers